Recent Study on Substrate Inhibition: Oxidation of D-Sorbitol and D-Dulcitol by Mn(VII) in Alkaline Medium - Latona , Dayo Felix; Akinola , Adegoke Emmanuel (Current Topics on Chemistry and Biochemistry Vol. 6, 2022)
The oxidation of D-sorbitol and D-dulcitol in alkaline medium by potassium permanganate revealed substrate inhibition for both substrates due to formation of a 1:1 manganese-sugar alcohol complex that resists oxidation. Consequently, the reaction was inverse first order with respect to sugar alcohol for both substrates, first order each with respect to [KMnO4], [OH-] and independent of ionic strength for both substrates investigated. Negative values of \(Δ\)S# suggests a rigid transition state, same \(Δ\)G# for the aminoalcohols reveals similar mechanism. The presence of a neutral molecule in the rate determining step was confirmed by the lack of ionic strength effect on the reaction rate. Furthermore,, absence of free radical formation was confirmed from the polymerization test. The product of the reaction via FTIR spectroscopy was a carboxylic acid.. Kinetic and spectroscopic studies led to the development of a plausible mechanism.